Comparative study of public policy on climate change in Latin America - Tavera Colonna, Jasmín (2014)
Although Peru is highly vulnerable to climate change, their ability to internalize this problem is weak, is handled as an environmental issue and not as an integrated set of policies and development actions. This reflects weak governance. CONAM, which depended on the Council of Ministers was in the right line, but without the necessary mechanisms for success on this line of decisions. In Peru, the issue focuses on improving the efficiency of processes, neglecting the demand side and the sustainability of the process. Climate change is a cross-cutting process that cannot cope with sector policy, it is not an environmental problem.